2019
DOI: 10.3390/jcm8122185
|View full text |Cite
|
Sign up to set email alerts
|

One-Stop Management of 230 Consecutive Acute Stroke Patients: Report of Procedural Times and Clinical Outcome

Abstract: Background and purpose: Rapid thrombectomy for acute ischemic stroke caused by large vessel occlusion leads to improved outcome. Optimizing intrahospital management might diminish treatment delays. To examine if one-stop management reduces intrahospital treatment delays and improves functional outcome of acute stroke patients with large vessel occlusion. Methods: We performed a single center, observational study from June 2016 to November 2018. Imaging was acquired with the latest generation angiography suite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 26 publications
(32 reference statements)
2
69
0
2
Order By: Relevance
“…Another potential shortcoming of a perfusion-based paradigm is that the emerging one-stop management for stroke treatment (utilizing a flat-detector CT in the angiography suite) has not been evaluated in large patient cohorts with perfusion-based triage paradigms so far [ 22 ], while collateral scoring functions relatively well [ 23 ]. This deprives late time-window acute stroke patients of a potential time-saving effect of up to 40 min due to a reduction of in-hospital time delays [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another potential shortcoming of a perfusion-based paradigm is that the emerging one-stop management for stroke treatment (utilizing a flat-detector CT in the angiography suite) has not been evaluated in large patient cohorts with perfusion-based triage paradigms so far [ 22 ], while collateral scoring functions relatively well [ 23 ]. This deprives late time-window acute stroke patients of a potential time-saving effect of up to 40 min due to a reduction of in-hospital time delays [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Psychogios et al reported study of 230 patients and a significant reduction of median door-to-reperfusion time (from 102 to 68 min; p < 0.001) and significantly better rate of good functional outcome (p = 0.029) in the one-stop management group [42]. Fewer radiation doses and fewer posterior fossa artifacts can be achieved by CBCT usage [42].…”
Section: Hospital Diagnosismentioning
confidence: 99%
“…Such a development will eventually allow for rapid patient selection and prompt treatment with IVT and EVT in eligible patients even in extended time windows. 155 …”
Section: Endovascular Treatment In the Anterior Circulation Before And After 6 H From Lswmentioning
confidence: 99%